The Feminization of Preschool Education Departments: Sociodemographic Profile, Social Background, and Gender Dimensions of a “Female” Career Choice - Gogou, Lela; Thanos, Theodoros; Nikolidakis, Symeon (European Journal of Social Science Education and Research, 2026)
This article explores the social dimensions of feminization in Preschool Education through an analysis of the sociodemographic profile of 192 male and female students in two departments at two Greek universities, namely the Department of Early Childhood Education and Care at the University of West Attica and the Department of Preschool Education at the University of Ioannina. Despite the global prevalence of female overrepresentation in the field, its systematic sociological analysis in the Greek context remains limited. The research is based on a quantitative methodology using a self-administered questionnaire completed by students within the university institutions. The findings reveal that the overrepresentation of women (96.4%) is not an expression of “natural inclination” but rather the result of socially constructed gender dispositions shaped by family socialization. The analysis documents the predominance of students from families with low and medium educational capital (46.3% first-generation students), the near-universal reliance on shadow education (84.4% attended a tutoring centre), and the stark gendered division of household chores from childhood through the university years. Chi-square tests further reveal that the more resource-intensive forms of shadow education and cultural participation remain socially stratified according to parental education. The study demonstrates that feminization constitutes a structural phenomenon arising from the inextricable intertwining of gender, class, and geographical relations of social reproduction, requiring an analysis that simultaneously examines these axes of inequality. The contribution of this research lies in the empirical documentation of the mechanisms that produce this gendered and social composition within the Greek context.